Stres akademik dan siklus menstruasi pada mahasiswi - Yulianti, Iis; Hermayanti, Yanti; Maryati, Ida (Holistik Jurnal Kesehatan, 2025)
Background: Academic stress was frequently experienced by students and was suspected to affect health, including the menstrual cycle in female students. An irregular menstrual cycle posed risks of dysmenorrhea, anemia, hormonal imbalance, and psychological disorders that impacted concentration and academic performance. Purpose: To identify the relationship between academic stress and menstrual cycle in female students. Method: A quantitative correlational design with a cross-sectional approach. Data collection was conducted in December 2024 using a Google Form-based questionnaire, namely the Perception of Academic Stress Scale (PAS) and menstrual cycle changes based on the American College of Obstetricians and Gynecologists. The sampling technique used total sampling, with a sample size of 145 female students and a response rate of 89.4%. Data were analyzed using descriptive analysis and Spearman's Rank correlation. Results: The majority of respondents experienced moderate levels of academic stress, a small proportion had irregular menstrual cycles, and no relationship was found between the two variables (p=0.522). Conclusion : No relationship was found between academic stress and the menstrual cycle in final-year female nursing students. It is recommended that the faculty conduct routine screening and counseling regarding academic stress and menstrual cycles. Female students are encouraged to manage stress and study strategies effectively, seek social support, and monitor their menstrual cycles. Suggestion: Future researchers are advised to consider other factors that may influence academic stress and the menstrual cycle, as this study did not find a relationship between the two variables.   Keywords: Academic Stress; Menstrual Cycle; Student.   Pendahuluan: Stres akademik sering dialami mahasiswa dan diduga dapat memengaruhi kesehatan, termasuk siklus menstruasi pada mahasiswi. Siklus menstruasi yang tidak teratur berisiko menyebabkan dismenore, anemia, ketidakseimbangan hormon, serta gangguan psikologis yang berdampak pada konsentrasi dan performa akademik. Tujuan: Untuk mengidentifikasi hubungan antara stres akademik dengan siklus menstruasi pada mahasiswi. Metode: Desain kuantitatif korelasional dengan pendekatan cross-sectional. Pengumpulan data dilakukan mulai Desember 2024 menggunakan kuesioner berbasis google form, yaitu Perception of Academic Stress Scale (PAS) dan perubahan siklus menstruasi berdasarkan American College of Obstetricians and Gynecologists. Teknik pengambilan sampel menggunakan total sampling dengan sampel 145 mahasiswi dan response rate 89.4%. Data dianalisis menggunakan analisis deskriptif dan korelasi Spearman's Rank. Hasil: Mayoritas responden mengalami stres akademik tingkat sedang, sebagian kecil memiliki siklus menstruasi tidak teratur, serta tidak ditemukan hubungan antara kedua variabel (p=0.522). Simpulan: Tidak ditemukan hubungan antara stres akademik dengan siklus menstruasi pada mahasiswi semester akhir. Saran: Peneliti di masa depan disarankan untuk mempertimbangkan faktor-faktor lain yang dapat memengaruhi stres akademik serta siklus menstruasi, karena pada penelitian ini tidak ditemukan hubungan antara kedua variabel.   Kata Kunci: Mahasiswi; Siklus Menstruasi; Stres Akademik.